Antiproliferative Effects of Alkaloids from the Bulbs of Crinum abyscinicum Hochst. ExA. Rich. (31st October 2020) - Abebe, Besufekad; Tadesse, Solomon; Hymete, Ariaya; Bisrat, Daniel
Abstract : Crinum abyscinicum Hochst. ExA. Rich bulb is traditionally used in Ethiopia for the treatment of various ailments including internal parasites, mastitis, rabies, colic diseases of animals, and cancer. Despite its importance in traditional cancer treatment, no research work has been reported on the antiproliferative activity of the bulb extract and its major constituents. Phytochemical investigation of the bulb extract of C. abyscinicum by PTLC over silica gel resulted in the isolation of two alkaloids, which were unequivocally identified as 6-hydroxycrinamine and lycorine on the basis of 1 H- and 13 C-NMR and MS analysis. The bulb extract, 6-hydroxycrinamine, and lycorine possessed significant antiproliferative activity, lycorine being the most active exhibiting GI50 values of 2.8  μ g/ml and 3.4  μ g/ml against A2780 and MV4-11 cells, respectively. Cell cycle analysis and annexin V/propidium iodide double staining in A2780 cells revealed that both compounds increased the percentage of cells in the S-phase at 30  μ g/ml without inducing apoptosis. Our results suggest that the antiproliferative activities of the bulb extract of C. abyscinicum, 6-hydroxycrinamine, and lycorine could support the traditional claim of the plant against cancer.